2014
DOI: 10.1177/0363546513518413
|View full text |Cite
|
Sign up to set email alerts
|

Does Degree of Trochlear Dysplasia and Position of Femoral Tunnel Influence Outcome After Medial Patellofemoral Ligament Reconstruction?

Abstract: This study demonstrates the importance of restoration of the anatomic insertion point of the MPFL when performing MPFL reconstruction and proposes that this procedure should not be performed in isolation in patients with high-grade trochlear dysplasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
137
3
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(147 citation statements)
references
References 36 publications
3
137
3
4
Order By: Relevance
“…18 Length changes of the reconstructed MPFL were most sensitive to femoral tunnel malpositioning, particularly in the proximal-distal axis. 17,18 Although graft isometry can be checked during MPFL reconstruction, intraoperative fluoroscopy has been recommended to guide femoral tunnel placement, 7,15 orientation at the anatomic landmarks described as the Schöttle point, 14 or the use of the 40%-50%-60% rule provided by Stephen et al 18 Nonetheless, the femoral tunnel was placed nonanatomically in 31% to 64% of reported MPFL reconstructions, 8,15 which suggests that femoral tunnel placement is prone to malpositioning, which may increase medial patellofemoral contact pressure and loss of knee flexion due to nonisometric length changes of the graft during knee joint motion. 17,18 Therefore, this study evaluated the sensitivity of femoral tunnel placement using lateral fluoroscopic guidance to minor degrees of hip abduction, adduction, and internal or external rotation.…”
mentioning
confidence: 99%
“…18 Length changes of the reconstructed MPFL were most sensitive to femoral tunnel malpositioning, particularly in the proximal-distal axis. 17,18 Although graft isometry can be checked during MPFL reconstruction, intraoperative fluoroscopy has been recommended to guide femoral tunnel placement, 7,15 orientation at the anatomic landmarks described as the Schöttle point, 14 or the use of the 40%-50%-60% rule provided by Stephen et al 18 Nonetheless, the femoral tunnel was placed nonanatomically in 31% to 64% of reported MPFL reconstructions, 8,15 which suggests that femoral tunnel placement is prone to malpositioning, which may increase medial patellofemoral contact pressure and loss of knee flexion due to nonisometric length changes of the graft during knee joint motion. 17,18 Therefore, this study evaluated the sensitivity of femoral tunnel placement using lateral fluoroscopic guidance to minor degrees of hip abduction, adduction, and internal or external rotation.…”
mentioning
confidence: 99%
“…10,21 Several groups of authors have specifically detected an association between trochlear dysplasia and poorer outcomes or outright failure following MPFL reconstruction. 8,10,21 Although they found a high rate of success of MPFL reconstruction in children and adolescents, Nelitz and colleagues 10 noted that 2 patients with high-grade dysplasia demonstrated a persistently positive apprehension test. Hopper et al 8 reported that only 9.3% of their patients with mild trochlear dysplasia developed recurrent dislocation postoperatively, compared with all 7 of their patients with severe dysplasia.…”
Section: Editorialmentioning
confidence: 99%
“…8,10,21 Although they found a high rate of success of MPFL reconstruction in children and adolescents, Nelitz and colleagues 10 noted that 2 patients with high-grade dysplasia demonstrated a persistently positive apprehension test. Hopper et al 8 reported that only 9.3% of their patients with mild trochlear dysplasia developed recurrent dislocation postoperatively, compared with all 7 of their patients with severe dysplasia. Similarly, Wagner et al 21 described a negative relationship between the degree of trochlear dysplasia and subjective outcomes.…”
Section: Editorialmentioning
confidence: 99%
See 1 more Smart Citation
“…Isometry of the reconstructed ligament is considered to be a prerequisite to a good outcome and an anatomical placement of the graft is the key to accomplish this [19].…”
Section: Introductionmentioning
confidence: 99%